Biomassa dan Cadangan Karbon Tegakan Kemiri (Aleurites moluccana Willd) - Erika, Erika; Wardah, Wardah; Naharuddin, Naharuddin (Universitas Tadulako, 2022)
This research was conducted to determine the biomass and carbon reserves of candlenut stands (Aleurites moluccana Willd), determine the effect of stand age on increasing biomass and carbon reserves, see the level of soil health and determine the relationship between stands. This type of research is descriptive which was carried out through surveys and data analysis using SPSS. The research results show that stand age has a positive effect on the amount of biomass and carbon stock produced. In 6 year old stands the average biomass = 12.23 tonnes/ha, and carbon 5.72 tonnes/ha, in 10 year old stands the average biomass = 23.23 tonnes/ha and carbon 10.87 tonnes/ha, 15 year old stands had an average biomass = 35.07 tons/ha and carbon 16.45 tons/ha. The correlation between age and biomass obtained by the equation The higher the age, the larger the stand diameter so that more biomass and carbon are produced. In addition, the high content of c-organics in the soil can maintain soil health levels.